Data Interoperability Between Elements of the Global Ocean Observing System - Snowden, Derrick; Tsontos, Vardis M.; Handegard, Nils Olav; Zarate, Marcos; O’ Brien, Kevin; Casey, Kenneth S.; Smith, Neville; Sagen, Helge; Bailey, Kathleen; Lewis, Mirtha N.; Arms, Sean C. (Frontiers in Marine Science, 2019)
The data management landscape associated with the Global Ocean Observing System is distributed, complex, and only loosely coordinated. Yet interoperability across this distributed landscape is essential to enable data to be reused, preserved, and integrated and to minimize costs in the process. A building block for a distributed system in which component systems can exchange and understand information is standardization of data formats, distribution protocols, and metadata. By reviewing several data management use cases we attempt to characterize the current state of ocean data interoperability and make suggestions for continued evolution of the interoperability standards underpinning the data system. We reaffirm the technical data standard recommendations from previous OceanObs conferences and suggest incremental improvements to them that can help the GOOS data system address the significant challenges that remain in order to develop a truly multidisciplinary data system.